Désir de distinction et dynamique sociale chez l’abbé de Saint-Pierre - Dornier, Carole (Lumen, 2021)
The Abbé de Saint-Pierre sought to develop a science regarding morals that aimed at “the greatest happiness of the greatest number.” In his system, heroic morality and Christian asceticism give way to merit, the service of the nation, and values devoid of any charismatic dimension. Against an intention-based approach inspired by Augustinianism and against Mandeville’s abandonment of self-interest, Saint-Pierre devised political institutions and collective educational programs that guided the desire of distinction toward public utility. Properly channelled, the pleasure of being distinguished becomes a dynamic principle that has the potential to produce a prosperous, harmonious, and benevolent society.